Rett syndrome and environmental enrichment as a potential therapy for attenuating the pathology - Tapia, Pablo (2019)
Rett syndrome (RTT) is a neurological disorder affecting the development of the central nervous system and one of the leading causes of mental retardation among young women. RTT patients exhibit microcephaly, decreased neuronal size, shorter cortical dendrite, and a reduced dendritic spine density; evidence strongly suggesting that a synaptic disorder underlies the neurological RTT-associated phenotype. MECP2 is a transcription factor with multiple roles on gene expression, and mutations in its gene coding sequence have been identified as the major cause of RTT. The generation of transgenic mouse models lacking the expression of Mecp2 has allowed getting insight into the physiopathological events associated with the loss of a fully functional Mecp2 allele in RTT patients and it has been demonstrated that is possible to partially rescue, or reverse, the phenotype associated with RTT which opens a window to explore therapeutic approaches plausible to be utilized in RTT patients. Considering that RTT patients exhibit reduced neuronal plasticity and synaptic disorder, this mini-review is focused on studies demonstrating the positive effect of an enriched environment on the RTT-like phenotype exhibited by mouse models of the disease.